Research and development of an intelligent controlled air exchange system for use in standard conditions based on iot - Dzhumabekova, Z. A.; Fazylov, N. N. (Харківський національний автомобільно-дорожній універститет, 2024)
The article discusses the basic principles of the Internet of Things (IoT) and embedded systems, as well as their interconnection and application in various fields such as smart homes, healthcare, industry and transport. The role of these technologies in improving the quality of life and increasing the efficiency of various processes is emphasized. Particular attention is paid to the prospects for the development of IoT in the context of the introduction of 5G technology, which is expected to contribute to a sharp increase in the number of connected devices and reduce energy consumption. It is expected that by 2021, the number of IoT devices in the world will reach 16 billion. The research is aimed at analyzing modern achievements in the field of IoT and identifying the challenges faced by these technologies, as well as considering their prospects in the context of digital transformation of society. The article also describes research methods, including theoretical analysis, comparative analysis, modeling and experimental testing. The results of the study show that the introduction of IoT and 5G technologies will lead to fundamental changes in society, business and production processes, opening up new opportunities for automation and optimization of various fields of activity.